2010
DOI: 10.1111/j.1460-9592.2010.03474.x
|View full text |Cite
|
Sign up to set email alerts
|

Serious hazards of transfusion in children (SHOT)

Abstract: Summary SHOT has been auditing information on transfusion practice for over ten years. Looking at this data allows us to determine the differences in the incidence of hazards seen in children compared to adults and to see which hazards are of particular importance for children of different ages undergoing surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
0
14
0
Order By: Relevance
“…The SHOT scheme [27] showed the estimation of the incidence of an adverse outcome to be 18:100,000 transfusions for children less than 18 years and 37:100,000 for infants less than 12 months, compared to 13:100,000 for adults. The SHOT classifies incidents reported into 12 different categories [28]; of these, IBCT event errors were the most common category in both adults and children, but they were particularly common in children, making up more than 80% of reports [26]. These findings suggest that pediatric patients are more vulnerable to transfusion-associated complications than adults.…”
Section: Preoperative Autologous Blood Donation and Transfusionmentioning
confidence: 81%
“…The SHOT scheme [27] showed the estimation of the incidence of an adverse outcome to be 18:100,000 transfusions for children less than 18 years and 37:100,000 for infants less than 12 months, compared to 13:100,000 for adults. The SHOT classifies incidents reported into 12 different categories [28]; of these, IBCT event errors were the most common category in both adults and children, but they were particularly common in children, making up more than 80% of reports [26]. These findings suggest that pediatric patients are more vulnerable to transfusion-associated complications than adults.…”
Section: Preoperative Autologous Blood Donation and Transfusionmentioning
confidence: 81%
“…32,33 More worryingly, the rate of complications, due to RBC transfusion, is higher in children than in adults and reported among infants to be up to three times as high. 34,35 Another study found an overall complication rate of 10.7 per 1000 units transfused in children compared to a rate of 2.5 in adults. 36 Plasma transfusion in critically ill children was in a recent prospective study independently associated with an increased occurrence of new or progressive multiple organ dysfunction syndrome, nosocomial infections, and prolonged length of stay in ICU.…”
Section: Paediatric Transfusionmentioning
confidence: 97%
“…* However, evolving challenges such as prion diseases (vCJD), malaria, dengue, babesia, and West Nile Virus are testing this notion. 4,34 Non-infectious risks Non-infectious serious hazard of transfusion (NISHOT) include human errors, accounting for the vast majority of these complications in children as well as in adults. 38 Alarmingly up to 82% of cases in infants and 58% in small children (less than 1 year old) appear to be due to human-related errors such as identification errors, laboratory errors, accidental over-transfusion, and lack of knowledge of special requirements.…”
Section: Infectious Risksmentioning
confidence: 99%
“…4 Allogenic transfusion is associated with potentially serious complications such as; incorrect blood component transfused (CMV+ blood to a CMV-patient), acute transfusion reactions, as well as transfusion-related acute lung injury. 19 Allogenic transfusion also increase the risk of infectious disease such as hepatitis B and C, HIV and nvCJD. 19 Predonation has several limitation in major spinal surgery such as difficulty of predicting which patients require blood tranfusion, 20,21 the high potential for wastage (up to 40% discarded autologous blood products), 20 a high level of communication across a variety of specialties necessary for successful implementation, and its inavailability in emergency surgeries.…”
Section: Estimated Blood Volumementioning
confidence: 99%
“…19 Allogenic transfusion also increase the risk of infectious disease such as hepatitis B and C, HIV and nvCJD. 19 Predonation has several limitation in major spinal surgery such as difficulty of predicting which patients require blood tranfusion, 20,21 the high potential for wastage (up to 40% discarded autologous blood products), 20 a high level of communication across a variety of specialties necessary for successful implementation, and its inavailability in emergency surgeries. 4 With the exception of the estimated blood volume, the baseline demographic variables between the PD and non-PD groups were similar.…”
Section: Estimated Blood Volumementioning
confidence: 99%